2013
DOI: 10.5152/jaem.2013.033
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cases That Composed Temporary Legal Report; Whom? When?

Abstract: Objective: Reports to legal authorities must be made for a variety of patients who present to emergency departments (EDs). This study summarises paediatric cases reported with a temporary legal form from our ED and reviews the literature on this topic with reasons and possibilities. Material and Methods: Charts were reviewed of all patients presenting to the university ED up to 18 years of age who were declared to hospital police as a legal case between January 1, 2008 and December 31, 2009. Demographic and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
1
5
0
2
Order By: Relevance
“…Pediatrik yaş grubu adli olgularda erkek cinsiyet genellikle daha fazla görülmektedir (9,(11)(12)(13). CDC verilerine göre ölümcül olmayan yaralanmalar 1-19 yaş aralığında erkek çocuklarda kız çocuklarına göre daha fazla görülmektedir (1).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Pediatrik yaş grubu adli olgularda erkek cinsiyet genellikle daha fazla görülmektedir (9,(11)(12)(13). CDC verilerine göre ölümcül olmayan yaralanmalar 1-19 yaş aralığında erkek çocuklarda kız çocuklarına göre daha fazla görülmektedir (1).…”
Section: Discussionunclassified
“…Öz kıyım girişimi, iş kazası, düşme gibi adli olayların birçoğunun arkasında çocuk istismarı ve ihmali olabileceği şüphesi göz önünde bulundurulmalı ve buna yönelik bulgular aranmalıdır. Çünkü acil servis başvurularında belirgin fizik bulgu ya da öyküsü olmayan çocuk olguların adli olgu olarak değerlendirilmediği ve ihbar edilmediği izlenmiştir (12). Yapılan çalışmalarda 2-17 yaş aralığıdaki olguların %80'nin hayatında en az bir kez %13 olgunun da hayatı boyunca iki veya daha fazla kez şiddete maruz kaldığı belirtmektedir (30,31).…”
Section: Discussionunclassified
“…However Çetinel et al [18] reported a rate Sexual abuse 1 100,0 0 0,0 *Includes cases of falls from the same level and from a height, ** Includes impact cases, hitting an object or hit with an object, ***Injury with sharp object, ****Firearm injury of 23.38%, higher than that generally stated in the literature. In our study poisoning cases (11.4%) were fourth in emergency services applications.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of these cases (64.7%) were male patients. In international studies the poisoning rate is approximately 12%, while national studies generally show wide variations in poisoning rates, ranging from 5% to 30% [9,10,13,18]. Many studies state that head-neck and upper extremity regions are the most frequently injured body areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation